Risk-Based Design for Slurry Launders - Janssen, RHA (Paste 2009: Twelfth International Seminar on Paste and Thickened Tailings, 2009)
A risk-based design approach using the principles of Six Sigma, has been applied to the design of open channel launders used to convey slurry in mineral processing plants. The variability in design input parameters was defined using a triangular probability distribution for the minimum, normal and maximum design values. Measured operating data, and results based on this measured data, were then compared to the risk-based results to assess the reliability of the risk-based approach. Where the operating data has a single most likely value, the triangular distribution was found to correctly capture the variation to be used in a risk-based analysis. However, where the operating data had a more complex distribution, this was not correctly captured in the usual design criteria of minimum, normal and maximum values. More detail, based on operational simulations or measured data from previous similar projects, should therefore be used in defining the system design criteria. The results presented here demonstrate the importance of collecting data to correctly define the variation of the input parameters for a risk-based analysis. In spite of not capturing the detailed shape of the measured data, the results of the risk-based design approach still provided a reasonable general description of the potential variation in design output. This can be used in making risk-based decisions for design, operating procedures, and capital investments.